Comparison of the role of milled glass and carbon fibers on mechanical properties of (bisphenol A)‐based epoxy composites. Issue 2 (27th February 2016) - Karimi, Saeed; Javadpour, Sirus
Abstract : The main target of the current work was to study the mechanical properties of milled E‐glass, S‐glass, and high‐strength (carbon fiber)‐reinforced epoxy composites. At first, tensile behavior of the as‐received fibers was evaluated by conducting different tensile tests. Afterwards, the effects of employing an integral blended coupling agent on the performance of the pure epoxy were investigated by microhardness tests and optical microscopic images. Then, the epoxy composites were prepared simply by mixing and stirring 1, 3, and 5 wt% of the milled fibers with the epoxy resin and its hardener. The effects of mixture degassing and addition of the coupling agent to the mixture were examined based on the mechanical properties of the fabricated composites. Also, scanning electron microscope macro‐ and micrographs of the transverse and longitudinal fracture surfaces were used to study the fracture behavior and identify the active toughening mechanisms. The best results were obtained for the degassed and modified milled (carbon fiber epoxy)‐reinforced composite, which enhanced the tensile strength, elongation, Young's modulus, and toughness up to 12%, 17%, 19%, and 27%, respectively. The current study shows that the composite not only is cost effective but also offers better mechanical properties. J. VINYL ADDIT. TECHNOL., 24:130–138, 2018. © 2016 Society of Plastics Engineers